Der Zauberstab der Analogie Untersuchungen zu den Erscheinungsweisen und Funktionen von Analogien in sprachlichen Sinnbildungsprozessen - Köller, Wilhelm (Studia Linguistica Germanica, 2023)
The publication aims to view analogy relations as heuristic magic sticks or semiotic universals through which the unknown can be heuristically opened up with the help of the known. This means that analogies simultaneously have analysing, synthesising and playful basic functions that can open up very diverse resonance spaces for us. It further implies that analogy assumptions also serve to bring the world of objects into a fruitful interaction context with the world of subjects. In this way, Cassirer's thesis that man is a genuine sign being (animal symbolicum), which can and must open up its life world with the help of cultural signs, can be exemplified very well.